2001
DOI: 10.1046/j.0022-202x.2001.01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Test Results but not Serology Reflect Immediate Type Respiratory Sensitivity: A Study Performed with Recombinant Allergen Molecules

Abstract: The diagnosis of type I allergy, an IgE-antibody-mediated hypersensitivity disease affecting more than 25% of the population, is based on the measurement of allergen-specific serum IgE levels and provocation testing. Whether the determination of allergen- specific serum IgE levels can replace in vivo provocation testing for allergy diagnosis is a controversial issue. We used purified recombinant timothy grass and birch pollen allergens to compare by skin prick and nasal provocation testing as well as by serolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 20 publications
(19 reference statements)
2
76
0
5
Order By: Relevance
“…Our results further suggest that not all cow's milkallergic patients show vigorous basophil degranulation with the intact allergen, although they did exhibit IgE Ab reactivity. Similar observations have been made for respiratory allergens where discrepancies between the IgE reactivities of allergens and their ability to induce basophil degranulation and in vivo allergic inflammation have been found (39). These findings may explain why the occurrence of clinical manifestations of cow's milk allergy does not always correlate with the presence of IgE Abs specific for milk allergens (40).…”
Section: Discussionsupporting
confidence: 63%
“…Our results further suggest that not all cow's milkallergic patients show vigorous basophil degranulation with the intact allergen, although they did exhibit IgE Ab reactivity. Similar observations have been made for respiratory allergens where discrepancies between the IgE reactivities of allergens and their ability to induce basophil degranulation and in vivo allergic inflammation have been found (39). These findings may explain why the occurrence of clinical manifestations of cow's milk allergy does not always correlate with the presence of IgE Abs specific for milk allergens (40).…”
Section: Discussionsupporting
confidence: 63%
“…32 Accumulating reports have shown striking differences in individual patients between SPT and serology test results suggesting an important role for the effector cells of immediate hypersensitivity (mast cells and basophils) and their activation during an allergic response. 32,[34][35][36][37] Therefore, there is a great need for a reliable in vitro method to complement the routine laboratory tests for sensitization/allergy when the latter show discrepancies or are not feasible. 33 Of note, Af-specific IgE levels correlated significantly with CD203c levels (Supporting Figure E7).…”
Section: Discussionmentioning
confidence: 99%
“…12 In a study comparing the performance of the SPT and sIgE with nasal allergen provocation using recombinant pollen allergens, Niederberger et al observed that SPT was more useful in predicting the allergenic potential for induction of respiratory symptoms than quantitative serology, as there was not a good correlation between the levels of sIgE and the biological tests. 24 Total serum IgE levels are frequently used to diagnose atopy, but their clinical value is limited due to the remarkable overlapping of IgE levels in both atopic and non-atopic individuals, in addition to the existence of a series of disorders that cause the elevation of tIgE, including intestinal helminthiasis. 25 In the current study, there was no statistically significant difference between the geometric mean of tIgE levels in asthmatics (591.7 kU/l) and in the controls (345.85 kU/l).…”
Section: Discussionmentioning
confidence: 99%